Nodule Initiation Involves the Creation of a New Symplasmic Field in Specific Root Cells of Medicago Species - Sauer, Norbert; et al. (The Plant Cell, 2003)
The organogenesis of nitrogen-fixing nodules in legume plants is initiated in specific root cortical cells and regulated by long-distance signaling and carbon allocation. Here, we explore cell-to-cell communication processes that occur during nodule initiation in Medicago species and their functional relevance using a combination of fluorescent tracers, electron microscopy, and transgenic plants. Nodule initiation induced symplasmic continuity between the phloem and nodule initials. Macromolecules such as green fluorescent protein could traffic across short or long distances from the phloem into these primordial cells. The created symplasmic field was regulated throughout nodule development. Furthermore, Medicago truncatula transgenic plants expressing a viral movement protein showed increased nodulation. Hence, the establishment of this symplasmic field may be a critical element for the control of nodule organogenesis.